Implementation of the Panel Model on Investment Determinants in Indonesia in 2018-2022 - Sihombing, Pardomuan Robinson; Arsani, Ade Marsinta; Nurul Islam, Iis Hayyun; Octaviana, Aniek; Maisaroh, Maisaroh (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2023)
Investment plays an essential role in the economic growth of a country. A country's ability to attract investment in various sectors can positively impact infrastructure development, job creation, and improving people's welfare. This study aims to determine the effect of the Gross Regional Domestic Product (GRDP), Regional Income, and Human Development Index (HDI) on investment in Indonesia. The variables of Domestic Investment and Foreign Investment measure investment. Data is sourced from the BPS-Statistics Indonesia for the 2018-2022 period—the statistical method used with multiple linear regression with panel data. Based on panel model testing, the PCSE model is the best. Simultaneously, all variables affect investment in Indonesia. Partially, GRDP, Regional Income, and HDI have a significant positive effect on investment in Indonesia. Based on the results of this study, comprehensive policies related to macro-social economics are needed so that the level of investment continues to increas.